Pengaruh Pendekatan Open Ended Terhadap Kemampuan Berpikir Kritis Matematika Siswa (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to describe students' critical thinking skills using the open ended approach and using the Scientific approach and to determine the effect of the open ended learning model on students' critical thinking skills. The research method used is a quasi-experimental design with a nonequivalent control group design with a population taken from class VIII A and B of SMP Masyithoh Kroya, Cilacap Regency. This research was conducted in September 2024. This study uses a quantitative research method. Data collection uses test, observation and documentation techniques. Validity uses professional judgment techniques. The data analysis technique uses the Mann-Whitney test after the analysis prerequisite test includes the normality test of distribution and the homogeneity test of variance. Based on the analysis carried out by the researcher, it can be concluded that the critical thinking skills of students in the experimental class after applying the open ended approach model got an average score of 36.62, and the control class using the Scientific approach got an average score of 28.39. The use of the open-ended approach model has a significant effect on students' critical thinking skills, this is proven by the results of the Mann-Whitney test which shows a high Asymp value. Sig.(2-tailed) = 0.000, which is less than the significance level of 0.05, from these results it is concluded that the Pythagorean open-ended approach has a significant effect on students' critical thinking skills in mathematics.